Peran Tokoh Agama dalam Menangani Penyebaran Covid-19 - Muchammadun Muchammadun; Sri Hartini Rachmad; Dendi Handiyatmo; Ayesha Tantriana; Eka Rumanitha; Zaenudin Amrulloh (UIN Sunan Gunung Djati Bandung, 2021)
This reseach examines the role of religious leaders in public health in the context of Covid-19 management. There are two arguments in this study. First, in the context of a religious society, religious leaders can play a socio-religious role through public health education. Second, the role will be effective as religious leaders analyze the media for providing da'wah public health material in accordance with the characteristics of the population. This article uses a descriptive method of analysis, which systematically describes facts and factual data. The data is then processed in a descriptive way to show how a phenomenon works. The primary data collected are The BPS survey on Community members’ behaviours on Covid-19 pandemic (BPS, 2020) and FGDs, analysed in the frame of related literature review. Results are reported in descriptive qualitative analysis. It is found that the community members’ obidinece on the Covid-19 health protocol is well influenced by the roles of sosial media, religious leaders’ suggestions, the population demographic characteristics and the enforcement of setup rules and policy.